1996
DOI: 10.1128/jcm.34.3.579-583.1996
|View full text |Cite
|
Sign up to set email alerts
|

Early neonatal diagnosis of congenital toxoplasmosis: value of comparative enzyme-linked immunofiltration assay immunological profiles and anti-Toxoplasma gondii immunoglobulin M (IgM) or IgA immunocapture and implications for postnatal therapeutic strategies

Abstract: Diagnostic strategies for congenital toxoplasmosis have changed profoundly in recent years. Immunological diagnostic methods, long considered disappointing, can now be used at a very early stage. Over a 3-year period, 1,050 infants at risk of congenital toxoplasmosis (born to 1,048 mothers infected during pregnancy) were monitored for a minimum of 12 months and a maximum of 7 years. More than 6,000 serum specimens were analyzed by comparative mother-infant immunological profiles (CIPs) based on an enzyme-linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(21 citation statements)
references
References 17 publications
1
19
1
Order By: Relevance
“…The fetal transmission rate was very high when seroconversion occurred during the third trimester, underlining the importance of early postnatal diagnosis in such cases, most of which escape antenatal diagnosis. IgM was detected by immunocapture in cord serum of 70% of the infected infants, and the combination of IgM and IgA immunocapture detection yielded the diagnosis in 80% of infected infants, a figure similar to those in other reports (4,13,19,40,47). Other investigators have achieved poor sensitivity (54%) of IgM detection at birth (22), although the specificity (91%) was similar to that observed in our study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The fetal transmission rate was very high when seroconversion occurred during the third trimester, underlining the importance of early postnatal diagnosis in such cases, most of which escape antenatal diagnosis. IgM was detected by immunocapture in cord serum of 70% of the infected infants, and the combination of IgM and IgA immunocapture detection yielded the diagnosis in 80% of infected infants, a figure similar to those in other reports (4,13,19,40,47). Other investigators have achieved poor sensitivity (54%) of IgM detection at birth (22), although the specificity (91%) was similar to that observed in our study.…”
Section: Discussionsupporting
confidence: 90%
“…These data suggest that this analysis should be repeated during the first 2 months of life or later when all other tests are negative. Pinon et al (39,40) reported on the value of enzyme-linked immunofiltration assay (ELIFA) for comparison of maternal and newborn IgG and IgM patterns. Using the ELIFA method, those investigators detected, within 60 days of birth, 67, 64, and 82.5% of infections by comparing the maternal and newborn IgG, IgM, and IgG plus IgM profiles, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning of the study (15 years ago), we discussed the protocol with our local ethics committee, who advised that written consent from a parent or guardian was not necessary. In collaboration with clinicians, we created the Reims Toxoplasmosis Group [1, 16], which managed the treatment of children with congenital toxoplasmosis (CT). Eighty鈥恘ine children were monitored prospectively by regular clinical and laboratory measurements from birth until 13.9 years old.…”
Section: Methodsmentioning
confidence: 99%
“…It is therefore necessary to have reliable and specific serological techniques for assaying IgG and IgM, as definitive diagnosis of Toxoplasma acute infection is critical for the clinical management of the mother and her fetus (4). All the SC must be accompanied with early treatment for the mother and lead to screening for the infection in the infant, whether prenatal or postnatal (5)(6)(7)(8)(9). Postnatal screening is based (i) on examination of the placenta, (ii) on a serological examination of the newborn, requiring techniques that are particularly sensitive and specific, for which the results will condition the treatment of the infant to limit later sequelae (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%